2020
DOI: 10.1111/1475-6773.13264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gentrification on adult mental health

Abstract: Objective: To estimate the net effect of living in a gentrified neighborhood on probability of having serious psychological distress. Data Sources:We pooled 5 years of secondary data from the California Health Interview Survey (2011)(2012)(2013)(2014)(2015) and focused on southern California residents. Study Design:We compared adults (n = 43 815) living in low-income and gentrified, low-income and not gentrified, middle-to high-income and upscaled, and middle-to high-income and not upscaled neighborhoods. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
1
42
1
Order By: Relevance
“…One found that compared to their counterparts in high income areas, both economically vulnerable and higher income older adults in gentrifying areas experienced more depression and anxiety symptoms [32]. The other found that low-income and long-term adults of gentrifying neighborhoods had a higher likelihood of serious psychological distress than those in low-income and not gentrified neighborhoods [38]. However, gentrification was not associated with the likelihood of having psychotic experiences [37].…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…One found that compared to their counterparts in high income areas, both economically vulnerable and higher income older adults in gentrifying areas experienced more depression and anxiety symptoms [32]. The other found that low-income and long-term adults of gentrifying neighborhoods had a higher likelihood of serious psychological distress than those in low-income and not gentrified neighborhoods [38]. However, gentrification was not associated with the likelihood of having psychotic experiences [37].…”
Section: Plos Onementioning
confidence: 99%
“…Multiple health outcomes were not associated with gentrification [19, 21, 23-25, 30, 36, 37, 48, 49]. Health outcomes that were associated with gentrification included: self-reported health [18,21,22,25,32,44], preterm birth [23], mental health conditions [19,32,38,44], alcohol and drug use [24,27,43,47], psychosocial factors [17,20,28,31,33,40,42,46,49], and health care utilization [26].…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations